Imprint of Mesoscale Eddies on Air-Sea Interaction in the Tropical Atlantic Ocean - Habib Micaël A. Aguedjou; Alexis Chaigneau; Isabelle Dadou; Yves Morel; Ezinvi Baloïtcha; Casimir Y. Da-Allada (Remote Sensing, 2023)
This study investigates the effect of mesoscale eddies on air–sea heat and fresh water exchange in the tropical Atlantic Ocean (TAO) using 8 years of satellite altimetry data, combined with sea surface temperature (SST), latent and sensible heat fluxes (LHF and SHF), infrared fluxes (IRF) and precipitation (PR) data. Results indicate that approximately ∼40% of cyclonic eddies contribute to warm SST anomalies, and ∼40% of anticyclonic eddies contribute to cold SST anomalies. Eddies were found to play a role in the variability in LHF, SHF and IRF, contributing 10–35% of their total variability, with the largest contributions observed beneath the intertropical convergence zone (ITCZ) and frontal SST areas. Composite analysis of SST and heat flux anomalies over eddies suggested that the anomalies created through horizontal advection processes may not significantly impact the overall LHF, SHF and IRF over eddies, contrary to vertical processes. Despite a lack of clear correlation between heat flux and PR anomalies over eddies in the TAO, significant correlations were found beneath the ITCZ, suggesting that eddies may impact both heat fluxes and PR in the ITCZ region. This study provides an original contribution to the understanding of the impact of ocean mesoscale eddies on the atmosphere in the TAO.